Long-term post-COVID-19 sequelae. A review study - Cinthia Rosales Márquez; Ericson Félix Castillo Saavedra (Medisur)
At present, investigations are more frequent in which it is reported that survivors of the SARS-CoV-2 infection do not regain their state of health prior to the viral process. The study collected information about the various sequelae recorded in original research indexed in databases such as Scielo, Scopus, and Pubmed, 11 articles were found from patients who had COVID-19, who participated in various studies in the post-acute stage of the acute disease process. the disease, some of them were even evaluated after 6 months of having started the symptoms, however, they continued presenting symptoms after the remission of the disease. In other articles, patients were evaluated by imaging tests such as computed axial tomography and cardiac magnetic resonance imaging. The results indicated sequelae in the respiratory system such as dyspnea, fatigue, lesions compatible with pulmonary fibrosis; while, in the cardiovascular system, sequelae such as tachycardia, palpitations, arterial hypertension, myocarditis and pericardial effusion were reported. Likewise, sequelae such as headache, ageusia, anosmia, insomnia, amnesia and concentration deficit were evidenced in the nervous system; In the musculoskeletal system, arthralgia, myalgia, difficulty moving, and, finally, in mental health, the conditions recorded were anxiety, post-traumatic stress disorder, depression, apathy, dysphoria, and feelings of inferiority.